A cross-sectional survey of employment status in patients with schizophrenia and its association with caregivers’ burden and quality of life - Semran KB,; Woon, LS; Marhani Midin,
Employment among patients with schizophrenia is known to positively influence patients’ recovery. In their crucial supporting role for patients, caregivers’ burden of care and quality of life may also be influenced by the employment status of patients. This study aimed to investigate the association between employment among patients with schizophrenia and burden and quality of life (QOL) of their caregivers. It was a cross-sectional survey among the primary caregivers of patients meeting DSM-IV-TR’s diagnostic criteria for schizophrenia who were under outpatient or community care at Hospital Bahagia Ulu Kinta. Socio-demographic data, including patients’ employment status, were collected. The Burden on Family Interview Schedule (BFS) and the 36-Item Short Form (SF-36) questionnaires were used to evaluate caregiver burden and quality of life, respectively. Altogether, 201 primary caregivers of patients with schizophrenia participated. Most caregiver burden was experienced in the aspects of finance and routine family activities. There was significant association between patient employment status (p<0.001), salary (p<0.001), duration of employment (p<0.001), and type of employment (p<0.001) with the level of caregiver burden. Caregivers of employed patients also had better QOL in the mental health aspect with significantly better mental component scores for SF-36 compared to the unemployed group (mean scores: 51.83 vs. 47.99, p<0.001). Supported employment programmes for patients with schizophrenia may also benefit their caregivers by reducing burden and improving quality of life.